A companion to biblical interpretation in early Judaism - Henze, Matthias 1965- (Eerdmans, 2012)
Presents eighteen commissioned articles on biblical exegesis in early Judaism, covering the period after the Hebrew Bible was written and before the beginning of rabbinic Judaism. --from publisher description